Welfare- and Trade-Based Indicators of National Distortions to Agricultural Incentives - Lloyd, Peter J. (Other papers, 2009)
Despite reforms over the past quarter-century, world agricultural markets remain highly distorted by government policies. Traditional indicators of those price distortions such as the nominal rate of assistance and consumer tax equivalent provide measures of the degree of intervention, but they can be misleading as indicators of the true effects of those policies. By drawing on recent theoretical literature that provides indicators of the trade- and welfare-reducing effects of price and trade policies, this paper develops more-satisfactory indexes for capturing distortions to agricultural incentives. It then exploits the agricultural distortion database recently compiled by the World Bank to generate estimates of them for both developing and high-income countries over the past half century, based on a sample of 75 countries that together account for all but one-tenth of the world's population, gross domestic product (GDP) and agricultural production. While they are still only partial equilibrium measures, they provide a much better approximation of the true trade and welfare effects of sectoral policies without needing a formal model of global markets or even price elasticity estimates